Day-ahead Economic Dispatch of Wind Integrated Power System Considering Optimal Scheduling of Reserve Capacity. (August 2015) - Chao, Luo; Jun, Yang; Zhi, Du; Jifeng, He; Mingsong, Liu
Abstract: This paper proposes a novel day-ahead dynamic economic dispatch model for the wind integrated power system, aiming to minimize the total cost of generation and reserve capacity of all units. The proposed model is formulated as a chance-constrained stochastic nonlinear programming (CSNLP) problem, in which the constraints of regulating characteristics of units are taken into account. A two-stage iterative algorithm, based on sequential quadratic programming (SQP) method and chance-constraint checking, is developed to solve the CSNLP efficiently. Finally, the proposed dispatch strategy is illustrated in an IEEE30 power system with six generators and a wind farm.